2005
DOI: 10.1177/0145482x0509901007
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and Preferences for Long Cane Components: A Qualitative and Quantitative Study

Abstract: This article reviews the literature on the various components of long canes and reports on a study of the knowledge and preferences of 100 adults with visual impairments regarding the various components and types of canes. Results indicated that the terrain of a route, weather conditions, mobility demand, and purpose of an outing are important factors when choosing a cane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As Farmer and Smith (1997) stated: "Travellers with vision impairments often express a strong preference" (p. 223). This assertion of strong preference in cane type by the user is supported in research by Ambrose-Zaken (2005). The experienced traveller might use more than one type of cane with different tips and these are determined by the environments in which the person travels.…”
Section: Evolution Of the Canementioning
confidence: 82%
See 1 more Smart Citation
“…As Farmer and Smith (1997) stated: "Travellers with vision impairments often express a strong preference" (p. 223). This assertion of strong preference in cane type by the user is supported in research by Ambrose-Zaken (2005). The experienced traveller might use more than one type of cane with different tips and these are determined by the environments in which the person travels.…”
Section: Evolution Of the Canementioning
confidence: 82%
“…The choice of brands increases and provides both the user and the O&M instructor many options. Knowing the characteristic of the cane and the needs of the user can lead to an informed decision regarding the type of cane to be used or constructed (Ambrose-Zaken, 2005).…”
Section: Evolution Of the Canementioning
confidence: 99%
“…However, they tend to fall into the following five categories: standard (pencil), marshmallow (teardrop), ball, roller, and metal (or ceramic) glide. In a survey conducted with 98 cane users in 2005, marshmallow tip was rated as the most preferred cane tip in three of six functional categories, which include durability, resiliency, and strength (Ambrose-Zaken, 2005). Although roller tips were not rated high in this survey, personal communications with one of the major cane tip vendors (T. Russell, personal communication, September 23, 2008) and orientation and mobility (O&M) specialists (A. Kaufman, personal communication, February 2, 2009; M. J. Weessies, personal communication, February 4, 2009; S. Williams-Riseng, personal communication, February 5, 2009) indicated that its popularity has been growing in recent years.…”
Section: Introductionmentioning
confidence: 99%